تغيّر قيمة النقد وأثره في سداد الدَّين (دراسة فقهية اقتصادية) - عبد الحق, الإمام (University of Eloued جامعة الوادي, 2017)
عرفت المجتمعات البشرية النقود بسبب صعوبات المقايضة, ثم استمر تطور النقود من حيث أنواعها ووظائفها. وكانت النقود الذهبية والفضية أفضل النقود التي عرفها الإنسان, لما لهذين المعدنين من خصائص ذاتية وتبادلية فاتّخذ المسلمون منها نقودهم وربطوا بها مختلف الأحكام الشرعية, وشددوا على ضرورة أداء النقود لوظائفها المختلفة ورغم هذا فإنّ هذه النقود ومع توسع النشاط التجاري بدأت تظهر في استعمالها بعض الصعوبات أدّت إلى ظهور النقود الورقية, وتعتري كل هذه النقود سواءا المعدنية منها أو الورقية عدّة مشاكل من بينها التغيّر في قيمتها لعدّة أسباب هي : الكساد والانقطاع, الغلاء والرخص, والتضخم. وقد تكلم عديد الفقهاء في مسألة تغير قيمة النقود جراء هذه الأسباب, ومن بين المسائل التي يمكن أن تناقش في حال تغيّر قيمة النقود هي كيفية أداء الدَّين الثابت في الذمة. وعليه فقد أسهم الكثير من العلماء والفقهاء في بحث هذه المسألة وعرض الطرق التي يمكن أن يؤدى بها الدَّين إثر التغيرات في قيمة النقود للأسباب السالفة الذكر. وأهم ما استنتجته في مسألة سداد الدَّين بعد تغيّر قيمة النقود أنّ الفقهاء لم يتفقوا على رأي واحد فكل حسب رأيه وتبريراته. لهذا وجب تكثيف الجهود أكثر للخروج برأي صواب ومتفق عليه. Human societies have known money because of the difficulties of bartering, and the development of money continued in terms of its types and functions. The gold and silver coins were the best money known to man, because these two minerals have autistic and reciprocal characteristics. Muslims took their money from them and linked them to the various legal rulings. They stressed the need for money to perform their various functions. However, this money and the expansion of commercial activity are beginning to show some difficulties. To the emergence of paper money, and see all this money, whether metal or paper, several problems, including the change in value for several reasons: recession and disconnection, high prices and licenses, and inflation. Many scholars have spoken about the change in the value of money for these reasons. Among the issues that could be discussed in the event of a change in the value of money is how the fixed debt is performed. Accordingly, many scholars and jurists contributed to the discussion of this issue and presented the ways in which religion can lead to changes in the value of money for the above reasons The most important conclusion in the issue of debt repayment after the change in the value of money that the jurists did not agree on one opinion, each according to his opinion and justifications. Therefore, more efforts must be intensified to come out with a correct and agreed opinion.
مذكرة ماستر تخصص معاملات مالية
Keywords: تغيّر.قيمة.النقود. سداد; change.values.money.payé